การวิเคราะห์ภัยพิบัติแผ่นดินไหวของสนามฟุตบอลในประเทศไทย - ภรภัทร พงศ์พัฒนศักดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
In the present time, football is one of the most popular sport in Thailand. In each game, there are many thousands of people come to a stadium to watch a match. The number of audiences depends on a stadium’s capacity and the interesting of a competing team. From the reason that I mentioned above, a football stadium is one of the places that attract people to gather. This senior project for estimate the seismic hazard in 34 football stadiums which I selected from teams that has their own stadium and can get attention from a large number of people. This project uses 2 methods for estimate the seismic hazard. They are Deterministic Seismic Hazard Analysis method (DSHA) and Probabilistic Seismic Hazard Analysis method (PSHA). The PSHA method uses 2% and 10% POE in 50 year and 100 year. From the estimated, the stadium in the northern and western parts of Thailand have higher peak ground acceleration (PGA) than the others. From DSHA method, the maximum PGA value is 0.37g in the Phrae United’s stadium. By the PSHA method 2% and 10% POE in 50 year and 100 year, the maximum PGA value is still in the Phrae United’s stadium. The values are 0.49g 0.56g 0.33g and 0.39g respectively. There are 3 stadiums in the risk of seismic hazard for Eurocode 1998 standard include Phrae United’s stadium, Chiangrai United’s stadium and Lampang FC’s stadium.